Should be halal? is there any correlation between halal and vaccine? bibliography study in SCOPUS indexed academic paper - Akhmad Kusuma Wardhana (Journal of halal product and research (JPHR), 2020)
Vaccine is the best way to tackle the virus outbreak, because vaccines could reprogram immunity systems to create their own antibodies. Muslims are obliged to consume only halal product. Vaccine needed to follow halal standardization to be used in Islamic countries. This study has a purpose to observe the connection between halal and vaccine in research papers indexed by Scopus website. This study uses papers indexed in Scopus website as secondary data.  There are two kinds of data, based on the organization of co-authorship, and co-occurrence of authors’ topic. There are 46 numbers of data the organization of co-authorship and 68 of co-occurrence of authors’ topic. The data is analyzed using Vosviewer software. The result shows that topic of vaccine has connection to halal and fatwa/ or ulama council’s statement. Thus, non muslim countries such as USA and Australia have more relevance points than Muslim countries. Based on the keywords, there are topic about vaccine and COVID-19. In can be concluded that halal and vaccine is intertwined each other, especially in muslim countries.